Further Observations on Reported Earnings and Stock Prices. - O'Donnell, John L. (The Accounting Review, 1968)
The income reporting during 1949-1961 of all electric utility companies by 25 firms, had adopted accelerated depreciation for tax reporting purposes by 1956, but 18 firms elected to normalize reported earnings while 7 employed the flow-through procedure. That is to say, flow-through firms made no provision for deferred taxes, preferring to allow reductions in current taxes to be reported as part of current income. Prior to 1954 all companies were required to use straight-line depreciation for tax purposes with only minor exceptions. It is widely recognized that fixed charge coverage is a critical ratio in helping investment services to assign quality ratings to bond issues. Such ratings in their turn play a key role in helping to determine market prices. In short, a fixed charge coverage ratio is an important index of a firm's borrowing capacity in an industry where the bulk of external capital is raised by debt issues. The arguments supporting flow-through have been numerous and varied but the substantive points can be swiftly summarized.